YANG MEMPENGARUHI FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING - Efriyenti, Dian; Azmiana, Risca; L. Tobing, Vargo Christian; Wangdra, Ronald (JURNAL AKUNTANSI BARELANG, 2024)
Operating profit margin and financial leverage have increased and fluctuated but income smoothing has not completely increased, and vice versa. The practice of profit equalization phenomenon emerged to reduce fluctuations in reported profits. Another case that occurred at the Kimia Farma company, carried out profit equalization actions, allegedly marking up net profit in the 2019 financial report, in the financial report it was able to obtain a profit of IDR 132 billion. However, the reported profit is different from the actual profit of IDR 132 billion. However, the reported profit was IDR 99 billion. In another case at Indofarma Tbk, goods were found to be of higher value than they should be. As well as having an impact on profits. The aim of this research is to analyze operating profit margin and financial leverage which have an impact on income smoothing. The population in this study is the number of food and beverage companies registered on the IDX. The sampling technique used criteria so that there were 14 samples in this study. Data analysis using regression analysis. The results obtained were up to 8 companies that experienced fluctuating data from operating profit margin and financial leverage as well as income smoothing. The research results state that financial leverage has no significant effect on income smoothing, while operating profit margin has an effect on income smoothing.